DEVELOPING TEACHING MATERIAL FOR PHYSICS BASED ON COLLABORATIVE CREATIVITY LEARNING (CCL) MODEL TO IMPROVE SCIENTIFIC CREATIVITY OF JUNIOR HIGH SCHOOL STUDENTS - Astutik, Sri; Prahani, Binar Kurnia (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2018)
The teaching material for Physics based on collaborative creativity learning (CCL) model is by design to improve scientific creativity, collaborative skills, and science process skills of junior high school students. The focus of this research is to analyze the teaching materials based on CCL model in terms of their validity (content and construct, reliable) and effectiveness to improve students? scientific creativity in the science lesson, particularly for Physics education. The validity and effectiveness of the teaching material were measured by using Validation Assessment Sheet (VAS) and Scientific Creativity Assessment Sheet (SCAS). The data were analysed through mean validity score, Cronbach?s coefficient alpha, Wilcoxon test, N-gain, and Mann Whitney test. The results of this study include: (1) validity of the the CCL-based teaching materials for Physics fulfill validity criteria (valid and reliable); (2) in terms of components of validity, the CCL-based teaching materials for Physics: (a) there is an increase of students? scientific creativity with the alpha of ? = 0.05, (b) the average score of students? scientific creativity was in medium category, and (c) there is no significant different improvement (consistent) of scientific creativity skills in all groups. The implication of this developmental research of CCL-based teaching materials for Physics has proven to be valid and effective to increase the scientific creativity of junior high school students, particularly in Motions and Simple Machine chapters.